Improved The Ability To Write Explanation Text Complex Through Stad Models In It Al Fattah Desa Lama Private High School Students - Nazra Arif (UMSU, 2021)
Many activities are closely related to writing skills, for example making summaries, taking notes, writing minutes, writing various kinds of letters, writing activity plans, to the ability to write scientific papers. Writing complex explanatory text is writing that tells of an event that is arranged in an orderly manner. Meanwhile, the Student Teams Achievement Division (STAD) is a method that prioritizes good teamwork. The ability to write complex explanatory texts of class XI SMA SWASTA IT AL FATTAH Lma Village in cycle I was (52%) complete learning and (48%) students have not finished learning. Then after taking the action in cycle II, the learning outcomes are (95%) complete and (5%) have not finished learning Keywords: ability, writing, complex explanatory text, STAD.